The methodology for reactive power control to ensure voltage quality using fuzzy logic - Kholiddinov Ilkhombek; Sharobiddinov Mirzokhid; Kholiddinova Mashkhurakhon; Komolddinov Sokhib; Qodirov Afzal; Tukhtasinov Saidislomkhon (EPJ Web of Conferences)
The article discusses the relevance of various models in addressing the challenges of solving electrical supply issues, particularly in the context of monitoring and optimizing power distribution networks. Researchers describe unique algorithms proposed for different aspects of power systems, including voltage regulation and enhancement, such as reactive compensation and optimal capacitor deployment. The benefits of utilizing fuzzy logic for controlling reactive power and improving regulation are highlighted, along with assessments of future developments in this field. Comparisons are made with conventional methods, emphasizing the advantages of fuzzy control. The article provides descriptions of results obtained in real-world conditions. It serves as an interesting resource for specialists in electrical engineering, automation, and researchers engaged in utilizing fuzzy models in engineering systems.